THE STUDY ON AN INEQUALITY ISSUE IN MOTORCYCLE SAFETY: A CASE STUDY OF BANGKOK - Iamtrakul, Pawinee; Chayphong, Sararad (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
The increasing number of road accidents and its negative impact has become a major concern issue across the undeveloped and developing countries. The main purpose of the study is to understand transportation inequalities and road safety by collecting several sets of data from different dimensions which include socio-economic background, traveling patterns, modes, and problems related to travel. To reflect the inequality of current safe travel in Bangkok, 1,040 samples (1,000 from questionnaire, 40 from focus group) from various groups including government agencies and private sectors in Bangkok were interviewed followed by a questionnaire and focus group. However, the analysis results indicated that low levels of safety issues are being experienced by motorcyclists, bicycle riders and pedestrians; and these categories are the most vulnerable commuters. This study also found that the unequal access position of safe traveling not only depends on the users’ ability to pay but also in most cases, it occurs due to a lack of sound policy as well as poor safety measures management from the policy level.